Avaliação dos efeitos antinociceptivo e anti-inflamatório da fração hidroalcoólica e da substância isolada, peltatosídeo, provenientes das folhas de Annona crassiflora Mart. em camundongos - Cristina da Costa Oliveira (2015)
Annona crassiflora Mart. is a tree native of the Brazilian Cerrado, popularly known as araticum or marolo, and it has been used in folk medicine for the treatment of inflammatory and painful diseases. Quercetin-3-O--D-glycopyranosil (1 6)-O--L-arabinoside, known as peltatoside, is a natural substance isolated from the hydroalcoholic fraction of Annona crassiflora Mart. leaves with possible involvement in the therapeutic actions of this plant. Objective: Assess the analgesic and anti-inflammatory actions in vivo, both of Annona crassiflora Mart. leaves, and the peltatoside from this plant. Methods: To assess the analgesic properties, formalin test was used according to the method of Dubuisson & Dennis (1977) and adapted to mice by Hunskaar et al. (1985), the tail-flick test (D'Amour & Smith, 1941) and the paw withdrawal test (Randall & Selitto, 1957) were also utilized. To analyze motor performance, we used the rota-rod test (Dunham & Miya, 1957). Furthermore, to assess the anti-inflammatory properties, the filtrate from the hydroalcoholic fraction of Annona crassiflora Mart. leaves was administered orally 1 hour prior to intrathoracic injection of carrageenan (200 µg), zymosan (200 µg), LPS (250 ng) or CXCL8 (60 ng) and neutrophil recruitment was assessed 4 hours after injection. In order to determine the role of endocannabinoids in the peripheral antinociceptive effect of peltatoside, we used: (i) VDM11, an endocannabinoid reuptake inhibitor; (ii) MAFP, a potent irreversible inhibitor of anandamide amidase; (iii) and JZL184, an irreversible inhibitor of monoacylglycerol lipase (MAGL), the main enzyme responsible for degrading the endocannabinoid 2-araquidonoilglicerol (2-AG). Statistical analysis: One-Way or Two-Way ANOVA followed by Bonferroni post-test. Results: Oral pretreatment with the filtrate from the hydroalcoholic fraction of Annona crassiflora Mart. leaves (53 mg/kg) decreased the licking time in the second phase of formalin test, which corresponds to inflammatory pain (P<0.05). The latency time (s) in the treated group in the tail-flick test has not changed, compared to the control group, suggesting that there was not central antinociceptive effects, probably only peripheral mechanisms involved. Once the formalin test and tail flick test involve motor responses, the rota-rod test was also conducted and it was found that the motor performance has not been altered by treatment (53 mg/kg). Moreover, the filtrated from the fraction of hydroalcoholic Annona crassiflora Mart. leaves significantly inhibited the recruitment of neutrophils into the pleural cavity induced by carrageenan (200 g), LPS (250 ng) and CXCL8 (60 ng), but not zymosan (200 g). Finally, the peltatoside (100 g/paw) produced a local inhibition of hyperalgesia induced by carrageenan (200 g/paw) in the paw withdrawal test. The antagonist for cannabinoid CB1 receptor (AM251, 80 g/paw) antagonized the antinociceptive effect induced by peltatosde, but not the antagonist for cannabinoid CB2 receptor (AM630, 100 g/paw). VDM11 (2,5 µg/pata), MAFP (0,5 µg/pata) and JZL184 (3,75 µg/pata) did not induce antinociception, when used alone, however, when administered with an intermediate dose of peltatoside (50 g/paw) potentiation was observed. Discussion: The experimental data show that the filtrated from the fraction of hydroalcoholic Annona crassiflora Mart. leaves possesses remarkable anti-inflammatory and antinociceptive activities. Furthermore, the results suggest that peltatoside is capable to inducing analgesia through activation of peripheral CB1 receptors, involving endocannabinoids. Financial support: CNPq, CAPES and FAPEMIG.